2004
DOI: 10.1515/cclm.2004.082
|View full text |Cite
|
Sign up to set email alerts
|

The emerging value of P-selectin as a disease marker

Abstract: Activated platelets are key components in many arterial disorders. P-selectin is an activation-dependent platelet receptor, which is also identified in endothelial cells. Together with E- and L-selectin it constitutes the selectin family. These transmembrane proteins have continued to attract great interest as they support rapid and reversible cell adhesion in flow systems and thus play an essential role in multicellular interactions during thrombosis and inflammation. Similarly to other lectins, selectins bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
87
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 74 publications
5
87
0
1
Order By: Relevance
“…In addition, it appears that elevated urinary VCAM-1 levels may persist even after active renal inflammation subsides ( Figure 2). P-selectin is an adhesion molecule that is expressed on platelets and several other cell types, and the level of P-selectin has been reported to be elevated in other autoinflammatory diseases, in which it has also been recognized as a circulating disease marker (11)(12)(13). The prominence of P-selectin in experimentally induced immune nephritis has also been quite extensively studied (34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it appears that elevated urinary VCAM-1 levels may persist even after active renal inflammation subsides ( Figure 2). P-selectin is an adhesion molecule that is expressed on platelets and several other cell types, and the level of P-selectin has been reported to be elevated in other autoinflammatory diseases, in which it has also been recognized as a circulating disease marker (11)(12)(13). The prominence of P-selectin in experimentally induced immune nephritis has also been quite extensively studied (34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we sought to determine the pathophysiologic relevance of these 4 molecules in immune nephritis. Some information is already available concerning the role of VCAM-1, P-selectin, and TNFRI in renal disease (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), as discussed below. However, much less is known about the role of CXCL16, which is a chemokine expressed on dendritic cells and macrophages.…”
Section: Vcam-1 P-selectin Tnfri and Cxcl16 In Nephritic Urinementioning
confidence: 99%
“…Perhaps of greater significance is that a number of ex vivo human studies showed that statins downregulate the soluble concentration of these molecules. Shed (soluble) adhesion molecules are well-known markers for atherosclerotic disease (36)(37)(38), and several studies indicated that statins down-regulate circulating soluble ICAM-1, vascular cell adhesion molecule 1 (39)(40)(41), and E-and P-selectin (42,43). However, not all studies that examined the effects of statins on the soluble levels of these molecules have replicated these findings (44,45).…”
Section: Statins As Antiinflammatory Drugs: Effects On Cells and Tissuesmentioning
confidence: 99%
“…VWF originates from endothelial cells and platelets (30,31) and is increased in various pulmonary diseases, including acute bronchitis (32), acute lung injury (33), and pulmonary hypertension (34). P-selectin, which also originates from endothelial cells and platelets (35)(36)(37)(38), may be elevated under certain circumstances in asthma (37)(38)(39) and is increased in other diseases, including hemolytic uremic syndrome, thrombotic thrombocytopenic purpura, and acute myocardial infarction (35,36,40). VWF is synthesized as pro-VWF and cleaved in the endothelial cell secretory apparatus into N-terminal polypeptide (VWFpp) and Cterminal mature protein (VWF:Ag); VWFpp and VWF:Ag may be secreted constitutively or stored as a complex in Weibel-Palade granules ( Figure 2A) (30,31).…”
mentioning
confidence: 99%
“…P-selectin is a type-I membrane protein sequestered in Weibel-Palade granules. The granules translocate to the endothelial surface in response to inflammatory and thrombogenic mediators, resulting in secretion of VWFpp and VWF:Ag and cell-surface display of P-selectin and its subsequent proteolytic release ( Figure 2A) (30,31,35,36,(41)(42)(43). Platelet a-granules also contain P-selectin and VWFpp and VWF:Ag; animal studies indicate that platelets are a major source of plasma Pselectin, whereas most VWF originates from endothelial cells (30,35,36,44).…”
mentioning
confidence: 99%